Ikaros Induces Quiescence and T-Cell Differentiation in a Leukemia Cell Line - Kathrein, Katie L. (American Society for Microbiology, 2005)
Ikaros is a hematopoietic cell-specific zinc finger DNA binding protein that plays an important role in lymphocyte development. Genetic disruption of Ikaros results in T-cell transformation. Ikaros null mice develop leukemia with 100% penetrance. It has been hypothesized that Ikaros controls gene expression through its association with chromatin remodeling complexes. The development of leukemia in Ikaros null mice suggests that Ikaros has the characteristics of a tumor suppressor gene. In this report, we show that the introduction of Ikaros into an established mouse Ikaros null T leukemia cell line leads to growth arrest at the G(0)/G(1) stage of the cell cycle. This arrest is associated with up-regulation of the cell cycle-dependent kinase inhibitor p27(kip1), the induction of expression of T-cell differentiation markers, and a global and specific increase in histone H3 acetylation status. These studies provide strong evidence that Ikaros possesses the properties of a bona fide tumor suppressor gene for the T-cell lineage and offer insight into the mechanism of Ikaros's tumor suppressive activity.